Polyurethane cum hydrophobic finishing of acrylic fabrics for enhanced comfort characteristics. Issue 3 (3rd May 2016) - Raza, Z.A.; Anwar, F.; Ahmad, N.; Rehman, A.; Nasir, N.
Abstract : Purpose: The paper aims to improve the protective and comfort properties of both woven and knitted acrylic fabrics by applying a hybrid waterborne polyurethane/fluorocarbon hydrophobic finish. Design/methodology/approach: In this study, it was found that the transportation of water from fabrics is one of the important textile parameters. To improve this property, a polyurethane-based finish (Dicrylan BSRN ® ) and an oil- and water-repellent finish (Oleophobol ZSR ® ) were applied by using the pad-dry-cure method. After applying the finishes, the resultant fabric samples were investigated for various textile properties. Findings: The application of Oleophobol ZSR ® increased the absorbency time, indicating that the fabric became hydrophobic, whereas the application of Dicrylan BSRN ® finish improved the moisture management properties of the woven acrylic. The tensile strength of the woven acrylic fabric was not significantly affected by the application of these finishes. The contact angle of treated knitted fabrics increased and air permeability decreased with an increase in the concentration of Oleophobol ZSR ® . Practical implications: Moisture management is one of the crucial performance criteria in today's apparel industry. Therefore, fluorochemicals are one of the major precursors used in water-repellent finishes and waterproof membranes in outdoor garments. Based on this fact, this research work focused on the textile sector, where moisture management is required. Originality/value: This is the first report about the combined application of waterborne polyurethane and fluorochemical-based finishes on acrylic fabrics to tune their comfort and hydrophobic properties.